Incomplete Resection of Necrotic Bowel May Increase Mortality in Infants with Necrotizing Enterocolitis - Garg, Parvesh Mohan (Pediatr Res, 2020)
BACKGROUND: Infants with advanced NEC often need surgical resection of necrotic bowel. We hypothesized that incomplete resection of NEC lesions, signified by the detection of necrotic patches in margins of resected bowel loops, results in inferior clinical outcomes. METHODS: We reviewed the medical records of infants with surgical NEC in the past 15 years for demographic, clinical, and histopathological data. We also developed statistical models to predict mortality and hospital stay. RESULTS: Ninety infants with surgical NEC had mean (± standard error) gestational age 27.3±0.4 weeks, birth weight 1008±48 g, NEC onset at 25.2±2.4 days, and resected bowel length of 29.2±3.2 cm. Seventeen (18.9%) infants who had complete resection of the necrosed bowel had fewer (4; 23.5%) deaths and shorter lengths of hospital stay. In contrast, a group of 73 infants with some necrosis within the margins of resected bowel had significantly more (34; 46.6%) deaths and longer hospital stay. The combination of clinical and histopathological data gave better regression models for mortality and hospital stay. CONCLUSION: In surgical NEC, incomplete resection of necrotic bowel increased mortality and the duration of hospitalization. Regression models combining clinical and histopathological data were more accurate for mortality and the length of hospital stay.